Front Cover: Charge generation in organic solar cells: Journey toward 20% power conversion efficiency. Issue 6 (26th December 2022) - Tamai, Yasunari
Abstract : Owing to the enormous contributions of many researchers, the power conversion efficiencies of organic solar cells (OSCs) now exceed 19%. In this review (e280 ), a photophysicist's views of charge generation in OSCs including exciton diffusion, charge transfer at donor:acceptor interface, and long‐range charge dissociation as well as future research directions for realizing further improvements are discussed.